2010
DOI: 10.1177/0021998310377935
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposites of poly(3,4-ethylenedioxythiophene) and montmorillonite clay: synthesis and characterization

Abstract: Poly(3,4-ethylenedioxythiophene) (PEDOT)/montmorillonite (MMT) clay nanocomposites were prepared for the first time, by exchanging exchangeable cations in the MMT interlayer with Ce(IV) followed by insertion of ethylenedioxythiophene monomer to result in spontaneous polymerization to give PEDOT—Ce(III)—MMT nanocomposites. The nanocomposites thus prepared were characterized by electrochemical methods, elemental analysis, X-ray diffraction (XRD), Fourier transform infrared spectroscopy, thermogravimetric analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 60 publications
1
14
0
2
Order By: Relevance
“…39 Unfortunately, PEDOT-MMT nanocomposites prepared by Letaïef et al 33 and Rajapakse et al 36 showed an intercalative structure rather than the more desirable exfoliated organization.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…39 Unfortunately, PEDOT-MMT nanocomposites prepared by Letaïef et al 33 and Rajapakse et al 36 showed an intercalative structure rather than the more desirable exfoliated organization.…”
Section: Introductionmentioning
confidence: 98%
“…9,[31][32][33][34][35] Some hybrid PEDOT-clay nanocomposites based on montmorillonite (MMT), which is a smectite group mineral clay that belongs to the general family of 2:1 layered silicates, have been reported in the last few years. 9,33,[36][37][38] Since exfoliated CP-MMT nanocomposites usually have better properties (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…For example, nanocomposites of polypropylene (PP) and polyethylene (PE), presenting both intercalated and exfoliated structures, have been obtained with clays modified by polymeric surfactants [4,5]. Nanocomposites of p-conjugated polymers and MMT have also been studied [6][7][8]. Among them are those of polythiophenes, a family of conductive polymers presenting functional groups which make them candidates for diverse applications such as microelectronic devices [9], catalysts [10], chemical and biosensors [11,12], among others.…”
Section: Introductionmentioning
confidence: 99%
“…Monomeric EDOT can be oxidatively polymerized by both electrochemical and chemical methods, in each case yielding a p-doped polymer with high conductivity (up to 500 S cm −1 ) [1,2]. PEDOT has been explored as the active or support material in a variety of applications encompassing charge storage devices [3], micro-electrochemical [4] and organic thin film [5] transistors, antistatic coatings [6], photovoltaic energy conversion [7], electrochromic and optical display devices [8,9], corrosion protection coatings [10], drug delivery [11], biosensors [12], electrocatalysis [13], memory devices [14], fluid handling devices [15] and mechanical actuators [16].…”
Section: Introductionmentioning
confidence: 99%